2021
DOI: 10.1111/hiv.13186
|View full text |Cite
|
Sign up to set email alerts
|

No overall impact on rate of weight gain with integrase inhibitor‐containing regimens in antiretroviral‐naïve adults

Abstract: Objectives: Integrase strand transfer inhibitors (INSTIs) are commonplace in modern antiretroviral therapy (ART). Increased weight gain with their use is increasingly scrutinized. We evaluated weight changes in treatment-naïve adults with HIV-1 attending a UK centre who started regimens including raltegravir or dolutegravir. Methods: A retrospective cohort study of adults prescribed an INSTI betweenJanuary 2015 and March 2020 were categorized as having started an ART regimen containing raltegravir, dolutegravi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…In our real‐world cohort, we did not observe a change in the rate of age‐ and sex‐matched BMI‐standardized z score after starting an ART regimen containing dolutegravir. These results are in line with the findings of several adult [3,4] and paediatric cohorts and trials [9,11] but contrast with some other studies [1,2,6–8]. Some HIV‐ and ART‐related factors associated with weight gain in adult randomized clinical trials were absent in most of our subjects, such as low baseline CD4 cell count, high baseline HIV RNA, and ART regimen containing tenofovir alafenamide [2].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our real‐world cohort, we did not observe a change in the rate of age‐ and sex‐matched BMI‐standardized z score after starting an ART regimen containing dolutegravir. These results are in line with the findings of several adult [3,4] and paediatric cohorts and trials [9,11] but contrast with some other studies [1,2,6–8]. Some HIV‐ and ART‐related factors associated with weight gain in adult randomized clinical trials were absent in most of our subjects, such as low baseline CD4 cell count, high baseline HIV RNA, and ART regimen containing tenofovir alafenamide [2].…”
Section: Discussionsupporting
confidence: 90%
“…Some studies in both naïve and ART-experienced adults suggested that INSTI-based regimens appeared to cause more weight gain and treatmentemergent obesity than non-INSTI combinations [1,2]. By contrast, no clear evidence of an overall increase in rate of weight gain following INSTI initiation was found in other observational adult cohorts [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…In these studies, greater weight gain and BMI changes were observed with INSTIs compared to both NNRTIs and PIs, although some noted similar weight trends between INSTI and PI therapy (Table 1). [9][10][11]19,45,46 Overall, the degree of weight changes on INSTI-based therapy were similar between prospective and retrospective studies in treatment-naïve patients. Typical weight changes Weight changes with INSTIs within a dual-therapy regimen have also been evaluated.…”
Section: Weight Change Comparisons Between Instis and Other Art Classesmentioning
confidence: 69%
“…In these studies, greater weight gain and BMI changes were observed with INSTIs compared to both NNRTIs and PIs, although some noted similar weight trends between INSTI and PI therapy (Table 1). 9-11,19,45,46…”
Section: Data Synthesismentioning
confidence: 99%
“…INSTIs were implicated as risk factors for weight gain in other observational studies as well [41,46], with very few reports reporting no association [47].…”
Section: Class Effects and Particular Antiretroviralsmentioning
confidence: 98%